Perceptions of Dating Violence: Assessment and Antecedents - Toplu-Demirtaş, Ezgi (Journal of interpersonal violence, 2022)
Challenging perceptions of violence is crucial to prevent dating violence (DV), because such perceptions intervene in the organization and interpretation of violent events. However, these perceptions have received limited attention. This likely reflects the lack of a psychometric tool to do so. The current study had two purposes: to develop a measure of perceptions of psychological, sexual, and physical DV, and to explore how vertical collectivism, through hostile sexism and violence myth acceptance, shapes perceptions of DV. A total of 491 college students (55.3% women; M = 20.76 years, SD = 1.77 years) completed measures of the vertical collectivism, hostile sexism, domestic violence myth acceptance, and perceptions of DV. The results of exploratory factor analyses revealed a 15-item single-factor measure of perceptions of DV as initial construct validity, which had satisfactory internal consistency. A gender difference emerged in perceptions of DV; college women perceived psychological, sexual, and physical DV as more serious compared with college men. Moreover, the association between vertical collectivism and perceptions of DV was serially mediated via hostile sexism and violence myth acceptance. The findings are discussed in terms of previous research and the need to address the role of vertical collectivism in sexism, myth acceptance, and perceptions of violence in prevention/intervention efforts to reduce vulnerability to DV perpetration and victimization. Several recommendations are outlined to facilitate future research.